Iatrogenic cortical aneurysm post-craniotomy - Zanini, Marco Antonio [UNESP]; Borges, Rodrigo Almeida; Henrique, Gustavo; Aquino, Nunes; Freitas, Carlos Clayton Macedo de [UNESP] (Taylor & Francis Ltd, 2010)
Taking into account the number of craniotomies performed every day around the world, iatrogenic aneurysm post-craniotomy is extremely rare with only anecdotal cases reported in literature. We report an iatrogenic aneurysm affecting a cortical vessel which probably developed during dural closure of a conventional craniotomy. The aneurysm was discovered 6 months after surgery on a routine control angiography. The patient was successfully treated by trapping the parent vessel and excising the aneurysm. Histopathological findings were compatible with a true type of traumatic aneurysm. The possibility of this rare condition occurring highlights the risk of arterial injury during craniotomy.</.